Combined molecular MRI and immuno-spin trapping for in vivo detection of free radicals in orthotopic mouse GL261 glioma - Towner, Rheal A. (2013)
Free radicals play a major role in gliomas. By combining immuno-spin-trapping (IST) and molecular magnetic resonance imaging (mMRI), in vivo levels of free radicals were detected within mice bearing orthotopic GL261 gliomas. The nitrone spin trap DMPO (5,5-dimethyl pyrroline N-oxide) was administered prior to injection of an anti-DMPO probe (anti-DMPO antibody covalently bound to a bovine serum albumin (BSA)–Gd (gadolinium)-DTPA (diethylene triamine penta acetic acid)–biotin MRI contrast agent) to trap tumor-associated free radicals. mMRI detected the presence of anti-DMPO adducts by either a significant sustained increase (p < 0.001) in MR signal intensity or a significant decrease (p < 0.001) in T1 relaxation, measured as %T1 change. In vitro assessment of the anti-DMPO probe indicated a significant decrease (p < 0.0001) in T1 relaxation in GL261 cells that were oxidatively stressed with hydrogen peroxide, compared to controls. The biotin moiety of the anti-DMPO probe was targeted with fluorescently-labeled streptavidin to locate the anti-DMPO probe in excised brain tissues. As a negative control a non-specific IgG antibody covalently bound to the albumin–Gd-DTPA–biotin construct was used. DMPO adducts were also confirmed in tumor tissue from animals administered DMPO, compared to non-tumor brain tissue. GL261 gliomas were found to have significantly increased malondialdehyde (MDA) protein adducts (p < 0.001) and 3-nitrotyrosine (3-NT) (p < 0.05) compared to normal mouse brain tissue, indicating increased oxidized lipids and proteins, respectively. Co-localization of the anti-DMPO probe with either 3-NT or 4-hydroxynonenal was also observed. This is the first report regarding the detection of in vivo levels of free radicals from a glioma model.